Mission-Critical Internet of Things on the 6G Network: Services and Apps with Networking Architecture - Shah, A. F. M. Shahen; Karabulut, Muhammet Ali; Rabie, Khaled (IEEE, 2023)
Towards a future of fully autonomous and intelligent systems, sixth-generation (6G) wireless communication networks are expected to transform client services and apps via the Internet of Things (IoT). Together, the infrastructure and apps should facilitate and enhance intelligent administration of city services, workplaces, and everyday lives. In particular, mission-critical IoT (MC IoT), which is the connection of critical objects to the IoT network that are critical to human life and safety, is of utmost significance. This paper covers MC IoT visions, services, and applications, as well as networking infrastructure. First, visions toward 6G MC IoT are presented in the context of fundamental technological needs, trends, and use cases. Second, the emerging 6G MC IoT services and applications are described. Finally, a networking architecture for 6G MC IoT is provided. There are challenges to the implementation of robust and effective 6G MC-IoT services and applications which are mentioned and future research directions are presented.
Keywords: IoT; mission-critical IoT; Networking Architecture; Services and Apps; 6G; Automation & Control Systems; Computer Science; Engineering